Respuesta :

ANSWER

The limit is -4


EXPLANATION


   [tex] \displaystyle\lim_{x\to -2} \dfrac{x^2-4}{x+2} [/tex]


The numerator factors into (x-2)(x+2)


   [tex] \displaystyle\lim_{x\to -2} \dfrac{(x-2)(x+2)}{x+2} [/tex]


The (x+2) cancel out


   [tex] \displaystyle\lim_{x\to -2} (x-2) [/tex]


By direct substitution


   [tex] \displaystyle\lim_{x\to -2} (x-2) = -2 -2 = -4 [/tex]

[tex] \displaystyle
\lim_{x\to -2}\dfrac{x^2-4}{x+2}=
\lim_{x\to -2}\dfrac{(x-2)(x+2)}{x+2}=
\lim_{x\to -2}(x-2)=-2-2=-4 [/tex]